Orta Asya’da İşbirliği ve Bütünleşme: Kolektif Güvenlik Antlaşması Örgütü Örneği - Yesevi, Çağla Gül (Global Political Trends Center Istanbul Kültür University, 2013)
This study examines the Collective Security Treaty Organization and its effects on cooperation and unification processes among Central Asian states. It argues that cooperation and unification among Central Asian States are mainly affected by the international environment that has changed after 9/11 and the Afghanistan Operation. Regional Powers have cooperated with both the US and the Russian Federation in fighting against terrorism. Central Asian States have been considering their new path through independent foreign policy or interGstate cooperation and even unification.